Perbandingan Kualitas Layanan Ritel Swalayan Menggunakan Competitive Zone of Tolerance Based dan Importance-Performance Analysis - Arfan Bakhtiar; Mega Aulia Silviadara; Aries Susanty (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
Increased retail economic has had an impact on the Indonesian economy. Carrefour as an international company has a local company's competitor, Hypermart. In order for both companies to know the position of competing, then benchmarking done between them using CZIPA (Competitive Zone of Tolerance based Importance-Performance Analysis) method. The use of CZIPA methods is done to determine the priority of each self-service in making improvements. The dimension used is the retail dimension called RSQS (Retail Service Quality Scale). The goal to be achieved is to know the superior service quality indicators owned by Carrefour and Hypermart and to make priority services to be improved on both self-service using RSQS dimensions. Data collected through questionnaire with purposive sampling method to 133 people. Research finds the main problem facing Carrefour is self-service layout that does not facilitate consumers to find the desired product. At Hypermart, the main problem is that the products in the catalog are not always available.